2018
DOI: 10.1063/1.5007758
|View full text |Cite
|
Sign up to set email alerts
|

Wide operating window spin-torque majority gate towards large-scale integration of logic circuits

Abstract: Interconnected magnetic tunnel junctions for spin-logic applications AIP Advances 8, 055921 (2018); https://doi.org/10.1063/1.5007622Toward error-free scaled spin torque majority gates AIP Advances 6, 065304 (2016); https://doi.org/10.1063/1.4953672Non-volatile spin wave majority gate at the nanoscale AIP Advances 7, 056020 (2017); https://doi.Spin Torque Majority Gate (STMG) is a logic concept that inherits the non-volatility and the compact size of MRAM devices. In the original STMG design, the operating ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Such a multifunctional logic operation in a single spin device helps to reduce circuit complexity. [138,139] The sMAJ device displays robust durability over several cycles [129] (Figure 7d) and exhibits promising future potential applications.…”
Section: Lateral Spin Valve and Spin Logic Devices In Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Such a multifunctional logic operation in a single spin device helps to reduce circuit complexity. [138,139] The sMAJ device displays robust durability over several cycles [129] (Figure 7d) and exhibits promising future potential applications.…”
Section: Lateral Spin Valve and Spin Logic Devices In Graphenementioning
confidence: 99%
“…[145] For efficient cascading, similar input and output variable in the spin device is desired to avoid power loss due to repeated spin-to-charge conversion. [25,139]…”
Section: Cascadingmentioning
confidence: 99%
“…The fourth type of device is the spin-torque majority gate (STMG), but despite its great potential, it is rather unpopular. Its original idea was proposed by Nikonov (Intel) [186] and an upgraded version has recently been reported [187]. The majority gate returns a logical 'true' if and only if more than 50% of its inputs are 'true', so that the majority gate acts as an AND/OR gate depending on the third input.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…If there are three inputs, as shown in figure 25(a), the magnetic states of the junction area are determined by the majority of inputs, similarly to QCA operations. The main advantages of STMG lie in its simple structure, reconfigurability and the possibility of implementing the fan-out and cascading functions [187] (see section 11). This has great potential in relation to neuromorphic devices, as some STMG devices exhibit memristor behaviour, which is the basic function of a synapse, in which the signal depends on the DW position.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…In 2006, Imre et al [39] demonstrated the majority gate using nanomagnets (NMLs), where information is transmitted through adjacent nanomagnets via dipolar coupling. Several reports proposed the majority logic gate based on domain wall (DW) transported by spin current via spin-transfer torque (STT) [40][41][42]. However, the DW-based devices require relatively high current densities, which results in instability in the device due to joule heating [43].…”
Section: Introductionmentioning
confidence: 99%